Do voluntary sustainability standards increase countries' access to cocoa export markets? - Nina Grassnick; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2021)
Large chocolate manufacturers have committed themselves to only using certifiedcocoa beans and some governments want to increase the share of certified cocoaproducts consumed in their countries. Thus, Voluntary Sustainability Standards(VSSs) become quasi-mandatory for cocoa producers and grinders to ensure accessto these markets. Yet, their trade effects are unclear. We study the effect of a VSSon raw and processed cocoa exports. We use a unique dataset that contains the UTZCertified cocoa production quantity of cocoa-producing countries from 2010 to 2016.This allows us to estimate a gravity model of trade and analyse the effect of the shareof UTZ Certified cocoa production quantity in a country on the trade value of rawcocoa beans, cocoa powder, cocoa paste and cocoa butter. Our results show thatUTZ certification only enhances bilateral exports of cocoa beans and paste, while itreduces exports of cocoa butter and has mixed effects on cocoa powder exports.
Keywords: F14; Q17; Q18; 330; cocoa trade; UTZ Certified; voluntary sustainability standards; gravity model